Prediction of histopathological grade in gastric cancer using dual energy CT-derived synthetic extracellular volume fraction - Zhou, Hai-fei; Chen, Wei; Li, Jing-qi; Sun, Ai-yun; Guo, Li-li (Frontiers in Oncology, 2025)
PurposeTo investigate the relationship between the synthetic extracellular volume (ECV) fraction and the hematocrit (HCT)-based ECV fraction in gastric cancer patients and to evaluate its potential utility in predicting the pathological grade of gastric cancer.MethodsData from the derivation cohort consisting of 142 patients who underwent nonenhanced abdominal CT examination were collected, and the CT values of the abdominal aorta (CTA) and inferior vena cava (CTV) were measured separately. Using linear regression between CT attenuations and conventional hematocrit (HCTcon), calculation formulas were derived for the synthetic hematocrit of the abdominal aorta (HCTsyn, A) and the inferior vena cava (HCTsyn, V). A validation cohort of 62 gastric adenocarcinoma patients with dual-energy CT was analyzed to calculate synthetic ECV (ECVsyn, A and ECVsyn, V) using the derived formulas. Differences between synthetic and conventional ECV(ECVcon), and their efficacy in differentiating pathological grades, were compared.ResultsDerived formulas: HCTsyn,A% = 1.152×CTA - 12.311; HCTsyn,V% = 1.142×CTV - 11.229. In validation, HCTsyn,A and HCTsyn,V showed no significant difference from HCTcon (all P>0.05). HCTcon was strongly correlated with HCTsyn, A (r = 0.898, P < 0.01) and HCTsyn, V (r = 0.826, P < 0.01). ECVsyn,A and ECVsyn,V also did not differ from ECVcon (all P>0.05). ECVcon was strongly correlated with ECVsyn, A (r = 0.990, P < 0.01) and ECVsyn, V (r = 0.983, P < 0.01). All ECV metrics exhibited excellent and comparable efficiency in differentiating pathological grades.ConclusionsSynthetic ECV performs comparably to conventional ECV and predicts gastric cancer pathological grading effectively.